Type 1 diabetes mellitus in chronic insulin deﬁciency conditions - A. Yu. Surovtseva; E. M. Khardikova; M. A. Stepchenko (Медицинский вестник Юга России, 2021)
Mauriac syndrome is a severe complication of type 1 diabetes mellitus, manifested by growth retardation, impaired formation of secondary sexual characteristics, lack of libido, and hepatomegaly. Currently, the presented syndrome is quite rare. This is more related to the emergence of intensive insulin therapy, which keeps the level of daily glycemia within the tolerance of type 1 for diabetes mellitus. The article describes a clinical case of the development of Mauriac syndrome in a 21-year-old patient with decompensated diabetes mellitus and multiple complications. The patient was deprived of proper control over the condition of daily glycemia and full-ﬂedged insulin replacement therapy for a long because of unfavorable social and material conditions in the family, which contributed to the development of chronic insulin insuﬃciency and complications.